Concept of Teaching Profession Teacher As a Profession - Bakhrudin All Habsy; Moh. Fais Zainurrosid; Figo Adhura Setianto (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Teachers are people who carry out teaching or educational activities in a place, either in formal or non-formal educational institutions. Teachers are classified as a profession because teachers have expertise obtained through special education and training, which is stipulated and explained in Law number 14 of 2005 in Chapter IV Articles 8 to 12 which explain and determine the qualifications, competencies, and certification of teachers. Teachers are professional positions that have the main task of educating, guiding, teaching, directing, training, assessing, and evaluating students or learners. So in addition to being required to have competence, a teacher must also be able to develop attitudes and levels related to the development of learning and professionalism.